Pelatihan Pembuatan Big Book Terhadap Guru Di PAUD Santu Leonardus - Maria Fatima Mardina Angkur; Pelagia Trifonia Sartika; Maria Yosefrida Mandang; Imelda Awul (Unika Santu Paulus Ruteng, 2023)
The problem that is often found in the field is teacher creativity in making big book media, as found in PAUD Santu Leonardus where teachers experience problems in making learning media due to low teacher creativity. Thus the PkM team carried out this activity. The method of implementing this PkM is in the form of training and mentoring. The implementation of this PkM includes 4 (four) stages, namely program planning, program implementation, observation and evaluation, and reflection. At the planning stage: the PKM team coordinates with the school regarding the themes and sub-themes that will be made, coordination regarding the schedule of activities, location of activities with the school. After coordinating with the school, the PkM team prepared the tools and materials needed to make bigbook media. The next stage is the PkM implementation stage. This PkM was carried out for one month, namely in May 2022. Then the Observation and Evaluation stage was carried out; Based on the results of observations obtained data related to the enthusiasm of students while participating in learning activities. The last stage is the reflection stage; Students are very interested and very active in learning activities